A new mid-Cretaceous Apsilocephalidae (Diptera) with elongated mouthparts from Kachin amber - Feng, Qi; Jia, Xisen; Wang, Shengxiang; Ren, Dong; Wang, Yongjie (Zootaxa, 2026)
A new Cretaceous apsilocephalid genus and species, namely †Protapsilocephala longisetosa gen. et sp. nov. (Apsilocephalidae) is described from mid-Cretaceous Kachin amber (~99 Ma). Its mouthpart morphology indicates a nectarivorous feeding habit, suggesting a role as a pollinator during the Cretaceous. This finding offers critical fossil evidence for the evolution of specialized feeding ecology in lower brachyceran flies and highlights the morphological and ecological diversity of the Apsilocephalidae in the Mesozoic.